Blunted anticipatory stress responses on competition day in team sports athletes compared to individual sports athletes - Michael Page; Hanna L. Glandorf; Sarah H. Mallinson-Howard; Danial J. Madigan; Scott A. Dawson; Susan Jones; Owen Kavanagh (Comprehensive Psychoneuroendocrinology, 2024)
Knowledge of anticipatory stress responses before sports competitions is limited, thus this study examined the relationship between anticipatory stress in terms of salivary cortisol secretion in athletes on the morning of a competition and a comparison baseline day. Thirty-seven athletes collected three saliva samples over a 45-min period post-awakening (0, 30 and 45 min). Anticipatory stress was expressed as Area Under the Curve compared to ground (AUCg; total cortisol secretion). There was no significant difference in AUCg between baseline and competition days. However, a mixed two-factor ANOVA with day and sport type (individual vs. team) revealed a significant main effect of sport type (p < 0.01) and a significant interaction (p = 0.001). Individual athletes demonstrated increased AUCg on competition day compared to baseline, while team athletes demonstrated decreased AUCg on competition day compared to baseline. This blunting response was also observed when analysing the raw cortisol secretion levels upon awakening. These findings suggest there may be substantive differences in anticipatory stress between individual and team sport athletes.